Breakdown of government debt into components in euro area countries - Török László (Journal of Risk and Financial Management, 2022)
The pandemic that erupted in 2020 generated a significant increase in public debt, which is likely to draw the attention of economic policy and the economic profession to the evolution and sustainability of debt. This study first shows how the gross sovereign nominal consolidated government debt of the euro area member states developed between 2011 and 2019. Using conventional breakdown and correlation calculation methods, the study analyzes how closely the three components are related to the government debt ratio. The three components are: budget balance, economic growth, and real interest rates. The study then groups the member states into groups using the hierarchical cluster analysis of the SPSS program. The 'composite' rankings formed on the basis of the correlation coefficients proved to be well-understood, and the examined countries were given a clear position within the cluster. Finally, a verbal macroeconomic analysis of the member states in the same group follows in terms of the relevance of each component in the evolution of their public debt. The analysis shows that each independent variable had a significantly different effect on the change in the government debt ratio of each member state. The results and the correlations established can also be used later to examine the sustainability of public debt in the euro area.
Keywords: 330; government debt; Eurozone; components; cluster analysis